Impact of sodium alginate hydrogel containing bacteriophage peptides that specifically bind to the EtCab protein on the inhibition of Eimeria tenella infection - Hang Chen; Wenjing Zhi; Bingrong Bai; Faisal R. Anjum; Zhipeng Jia; Rui Kong; Qiuju Liu; Biao Wang; Chunli Ma; Dexing Ma (Veterinary Research)
Abstract Avian coccidiosis, caused by the protozoan Eimeria, leads to significant economic losses for the poultry industry. In this study, bacteriophages that specifically bind to the calcium-binding protein (EtCab) of Eimeria tenella were selected using a biopanning process with a pIII phage display library. The recombinant EtCab protein served as the ligand in this selection process. The binding ability of target phages to the EtCab protein or E. tenella sporozoites was evaluated. The role of peptides corresponding to target phages in inhibiting the invasion of E. tenella sporozoites into cells was analysed using flow cytometry. Subsequently, the phages were encapsulated in sodium alginate to protect them from degradation in gastric fluid, which has a low pH value. Chickens were orally administered both microencapsulated and non-microencapsulated phages, and the protective effects against E. tenella infection were assessed. The binding mechanism of these peptides to the EtCab protein was investigated through in silico analysis. The results indicated that three specific phages (Y, G, and V) could bind effectively to recombinant EtCab protein as well as to sporozoite proteins. All three peptides, particularly Y and G, demonstrated significant inhibition of sporozoite invasion into cells in vitro. Additionally, oral administration of the encapsulated phages Y and G provided a higher level of protection against Eimeria infection compared to encapsulated phage V and the unencapsulated phages. Molecular docking studies revealed that three peptides, particularly Y and G, efficiently bind to the EtCab protein through hydrogen bonds. This study provides a reference for developing small molecular drugs targeting coccidiosis.